The politics of multiracialism : challenging racial thinking - Dalmage, Heather M., 1965- (State University of New York Press, 2004)
"This is the first book to critically look at the political issues and interests surrounding the broadly defined Multiracial Movement and at what is being said about multiracialism. Many of the multiracial family organizations that exist across the United States developed socially, ideologically, and politically during the conservative Reagan years. While members of the Multiracial Movement differ widely in their political views, the concept of multiracialism has been taken up by conservative politicians in ways that are often inimical to the interests of traditionally defined minorities." "Contributors look at the Multiracial Movement's voice and at the political controversies that attend the notion of multiracialism in academic and popular literature, internet discourse, census debates, and discourse by and about pop culture celebrities. The work discusses how multiracialism, hybridity, and racial mixing have occurred amidst existing academic discussions of authenticity, community borders, identity politics, the social construction of race, and postmodern fragmentation. How the Multiracial Movement is shaping and transforming collective multiracial identities is also explored."--Jacket
Keywords: Multiracial people -- Race identity -- United States.; Race awareness -- United States.; Ethnicity -- United States.; Racism -- United States.; Multiracial people -- United States -- Social conditions.; Social movements -- United States.; United States -- Race relations.; Conscience de race -- États-Unis.; Ethnicité -- États-Unis.; Racisme -- États-Unis.; Mouvements sociaux -- États-Unis.; États-Unis -- Relations raciales.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Multiracial people -- Social conditions; Ethnicity; Race awareness; Race relations; Multiracial people -- Race identity; Racism; Social movements; United States